More than one story. (Simrishamn : Department of culture and leisure, 2015)
More Than One Story has proven to be a valuable tool for social workers, teachers, religious leaders, event coordinators and youth leaders. Wherever fears and prejudices tend to keep people isolated from those who seem different, More Than One Story is being used to facilitate the process of integration and inclusion, the opening of hearts and minds. Playing More Than One Story awakens empathy, compassion, understanding and appreciation for the unique experiences of each person; it brings strangers together and deepens communication amongst family and friends. The cards do not ask for opinions which can often lead to discussions. They ask for personal experiences and the feelings connected to them, feelings we all have in common. More Than One Story empowers individuals and organizations who wish to work for a more harmonious world.
Didactisch materiaal.
Keywords: Educatieve spellen; Gezelschapspellen